Respostas

2013-11-25T12:21:36-02:00
x² - 7x + 10 = 0
a = 1            b = - 7                 c = 10
∆ = b² - 4 . a . c 
∆ = (- 7)² - 4 * 1 * 10
∆ = 49 - 40
∆ = 9
x = - b + √∆
     ---------------
          2a
x = - (- 7) 
 + √9
      ------------------
            2 * 1
x = 7 + 3
      -------
         2
x' = 7 + 3 
         2
x' = 10 ÷ 2
x' = 5

x" = 7 - 3 
         2
x" = 4 
÷ 2
x" = 2
Resposta: {5, 2}
2013-11-25T13:45:50-02:00
Primeiro ache o que vai dentro da raiz!

Δ= (-7)² - 4 * (1) * (10) 
Δ= 49 - 40
Δ= 9 
Δ= raiz de 9= 3

agora jogue a fórmula de Bhaskara 

x1 = 7 + 3 / 2 = 5 
x2= 7-3 / 2 = 2